(untitled) (Global Scientific Review, 2022)
The article deals with the systemic relations of the Russian language, their role and interrelation. It is impossible to analyze lexical units separately; they must be considered in relation to each other. Systemic lexical relations include paradigmatic (level), syntagmatic (linear) and derivational